Load rating assessment of a corroded pier structure in the Gulf of Mexico - Torres-Acosta, Andrés Antonio; Martínez-Madrid, Miguel; Castro-Borges, Pedro; Aschermann, Scott; Commander, Brett; Grimson, Jesse (Revista ALCONPAT, 2018)
This work assesses the structural integrity of a pier located in the Gulf of Mexico through a live-load testing analysis of a corroded structure that withstands heavy loads. Procedures included instrumentation for load application of four different loads (50, 60, 350, and 700 Ton) to examine its structural performance, then calibrate the resultant finite-element models of the structure, and finally estimate the load rating factors using AASHTO methodology. Results showed that corrosion damages did not appear to represent an extreme structural menace; however, it was found that several piers’ structural elements are currently overloaded and need to be externally reinforced. This paper outlines the testing procedures, describing both the followed analysis and the data management criteria.